2004
DOI: 10.1038/sj.bmt.1704786
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of allogeneic CD34-selected stem cells after fludarabine-based conditioning regimen for children with mucopolysaccharidosis 1H (M. Hurler)

Abstract: Summary:Hurler syndrome (MPS1H) is a progressive inborn error of mucopolysaccharide metabolism leading to premature death. Allogeneic hematopoietic cell transplantation (HCT) can achieve stabilization and improve long-term survival. However, large studies have shown that preparative regimen-related toxicity (RRT) and graft failure rates have been relatively high. We transplanted five Hurler children with a fludarabine-based conditioning regimen, consisting of fludarabine/busulphan/ATG for matched family donor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…6 After a mean follow-up time of 43.6 months (range 32-59mo), all of our children showed progression of psychomotor development. Similarly to the findings of Staba et al, 13 we observed a more pronounced increase of psychomotor skills with a latency of several months after SCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 After a mean follow-up time of 43.6 months (range 32-59mo), all of our children showed progression of psychomotor development. Similarly to the findings of Staba et al, 13 we observed a more pronounced increase of psychomotor skills with a latency of several months after SCT.…”
Section: Discussionmentioning
confidence: 99%
“…The SCT relevant details have been communicated elsewhere. 6 Informed consent was obtained from the parents for the publication of case details.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 As a phase 2 study, the protocol was approved by the institutional review board and then distributed to other German centers willing to transplant children with inborn errors of metabolism. A total of 12 consecutive children were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Кроме того, в большинстве протоколов циклофосфамид заменен на флударабин с целью снижения токсичности, а для дополнительной миелоаблации (учитывая высокий потенциал отторже-ния) в терапию был добавлен мелфалан. Мелфалан и флударабин, в свою очередь, не обладают кардиоток-сичностью [11].…”
Section: актуальностьunclassified